Botánica médica de los indígenas cuna de arquía, chocó (1995)
A medical-botanical study in the indigenous Cuna community of Arquia (Choco) with the collaboration of the Inatuledi (botanical doctor) Claudio Izquierdo is presented. Different aspects about health, illness and the healing process are discussed. 146 plants are relerenced including indian language and translation, a brief description of uses and applications and the taxonomical name of 53 plants.